Zelman Abraham Waksman (on the Occasion of the 50th Anniversary of his Death) - Matselyukh, B.P.; Мацелюх, Б.П. (PH "Akademperiodyka" of the NAS of Ukraine, 2023)
On August 16, 2023, we will mark the 50th anniversary of the death of the well-known American microbiologist and biochemist, Doctor of Sciences, Professor, Nobel Prize laureate, and a native of Ukraine Zelman Abraham Waksman. He was born on July 22, 1888, in the village of Nova Pryluka, Vinnytsia region.